Aplikasi Jarenang Pada Bambu Sebagai Bahan Pembuatan Motif Pada Anyaman Rotan Di Kelompok Pengrajin - Yusintha Tanduh; Nursiah Nursiah; Desy Natalia Koroh (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
The purpose of accompaniment for craftsmen Jawet Kaladan group is to provide insight and knowledge of the importance of the quality of raw materials, while for the Silip group in the form of accompaniment and diversification of materials using natural materials from Jarenang (Dragon blood). Diversification carried out still apply the elements of the Dayak art form of a straight line and arches. Diversification carried out still apply the elements of the Dayak art form of a straight line and arches. The expected benefit is the craftsmen can improve the quality of raw materials and use the natural coloring material wrong with jarenang. The activities are carried out by initiating the socialization and introduction of tools and materials, followed by the implementation of the activities of bamboo cutting, clearing the outer layer of bamboo, bamboo stem division, separating the inner and outer layers of bamboo, drying the bamboo sheets, coloring the bamboo with the jelagah, giving the color with cruising, attenuate bamboo and tinker. After accompaniment and final evaluation of this service, crafters are expected to have the knowledge and skill of using the jarenang as a natural dye on the handicraft products they produce.